High Fat With High Sucrose Diet Leads to Obesity and Induces Myodegeneration - Rasool, Suhail; Geetha, Thangiah; Broderick, Tom L.; Babu, Jeganathan R. (Frontiers in Physiology, 2018)
Skeletal muscle utilizes both free fatty acids (FFAs) and glucose that circulate in the blood stream. When blood glucose levels acutely increase, insulin stimulates muscle glucose uptake, oxidation, and glycogen synthesis. Under these conditions, skeletal muscle preferentially oxidizes glucose while the oxidation of fatty acids (FA) oxidation is reciprocally decreased. In metabolic disorders associated with insulin resistance, such as diabetes and obesity, both glucose uptake and utilization muscle are significantly reduced causing FA oxidation to provide the majority of ATP for metabolic processes and contraction. Although the causes of this metabolic inflexibility or disrupted “glucose-fatty acid cycle” are largely unknown, a diet high in fat and sugar (HFS) may be a contributing factor. This metabolic inflexibility observed in models of obesity or with HFS is detrimental because high rates of FA oxidation in skeletal muscle can lead to the buildup of toxic metabolites of fat metabolism and the accumulation of pro-inflammatory cytokines, which further exacerbate the insulin resistance. Further, HFS leads to skeletal muscle atrophy with a decrease in myofibrillar proteins and phenotypically characterized by loss of muscle mass and strength. Overactivation of ubiquitin proteasome pathway (UPP), oxidative stress, myonuclear apoptosis and mitochondrial dysfunction are some of the mechanisms involved in muscle atrophy induced by obesity or in mice fed with HFS. In this review, we will discuss how HFS diet negatively impacts the various physiological mechanisms in skeletal muscle.